Technical Barriers to Trade and Firms' Export Decisions - Shuyao Yang (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper investigates the impact of restrictive TBTs on firms' extensive margins (export participation and exit probability), intensive margins (export value) and pricing strategy (export price). To this end, product-level restrictive TBTs and firm-level export are combined and an instrumental-variable approach is utilized. The results show that the imposition of restrictive TBTs adversely affect firms' intensive and extensive margins, but not significantly affect firms' price on average. More importantly, firms of different types, in the sense of firm sizes, number of destination markets and ownership types, are affected differently. Given the same restrictive TBTs, firms with higher productivity suffer less, while firms with lower productivity are more vulnerable to the trade barriers.
Keywords: F13; F14; 330; TBTs; firm heterogeneity; extensive margins; intensive margins; pricing strategy